Electromyographic analysis of select eccentric-focused rotator cuff exercises - Fukunaga, Takumi; Orishimo, Karl F.; McHugh, Malachy P. (Physiotherapy theory and practice, 2022)
BackgroundEccentric-focused rotator cuff exercises are clinically useful in rehabilitation; however, to what extent these exercises activate shoulder musculature is unknown.PurposeInvestigate peak electromyographic (EMG) activity of shoulder musculature during eccentric-focused rotator cuff exercises to inform clinical decision-making.MethodsSurface EMG activity was measured in 15 healthy subjects from 5 muscles of the dominant shoulder: supraspinatus, infraspinatus, upper trapezius, lower trapezius, and middle deltoid. Subjects performed 5 exercises: short-to-long scaption, sit-to-stand scaption, standing external rotation (ER), sidelying ER, and sidelying horizontal adduction. The effects of exercise and muscle on peak EMG activity were analyzed using two-way repeated-measures ANOVA and followed with post-hoc pairwise comparisons.ResultsSignificant exercise-by-muscle interaction effect was found (p < .001). Short-to-long and sit-to-stand scaption elicited higher activity in supraspinatus and middle deltoid compared to other exercises (p < .05); however, no effect of muscle was found for these exercises (p > .05). Infraspinatus and lower trapezius demonstrated higher activity compared to other muscles during standing ER, sidelying ER, and sidelying horizontal adduction (p < .05).ConclusionEccentric-focused exercises sufficiently activate the rotator cuff and is effective for use in rehabilitation. Caution must be taken as some exercises do not target specific musculature.